Synthesis of Titanium Dioxide Nanoparticles (3nm) by adding PEO - Yatim Lailun Ni'mah (Akta Kimia Indonesia, 2017)
Nanosized Titanium dioxide (TiO) powder was synthesized via hydrothermal  method using titanium tetrachlorida (TiCl4) as the precursor and add PEO (Mw = 600.000). The as prepared nano powder was used for further characterization. The phase transformation was investigated by an X-ray diffractometer (XRD). The grain size of the TiO2 particle was found to be 3.4 nm. Experimental results have shown that the as-prepared powders have entirely consisted with anatase crystalline phase.